2007
DOI: 10.1016/s0167-2991(07)80209-6
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 8 The role of cerium-based oxides used as oxygen storage materials in DeNOx catalysis

Abstract: Materials with high "Oxygen Storage Capacity" (OSC) are now widely used in automotive converter catalysts. There are mainly composed of Ce-based oxides (CeZrOx, CeZrPrOx, ...) having both multiple cationic valencies and oxygen vacancies. These properties allow the catalyst to store active O species (O 2-, superoxide, ...) in O2 excess and to release them when the O2 concentration in gas phase decreases or becomes nil. After having briefly examined the main properties of these OSC materials and the methods empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…According to Duprez et al [153], Ce-based oxides with cationic valences and oxygen vacancies may be considered as materials with high OSC. These properties allow for the storage of active oxygen species (O 2− , superoxide, etc.)…”
Section: Characterization Of Au/ceo 2 Catalysts Involved In Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Duprez et al [153], Ce-based oxides with cationic valences and oxygen vacancies may be considered as materials with high OSC. These properties allow for the storage of active oxygen species (O 2− , superoxide, etc.)…”
Section: Characterization Of Au/ceo 2 Catalysts Involved In Oxidationmentioning
confidence: 99%
“…in O 2 excess and their release when the partial pressure of oxygen decreases. The experimental procedure for OSC measurements implies the use of reductant molecule, often CO and less H 2 [153]. According to Yao and Yu Yao [154], the CO 2 produced during the first CO pulse allows for the calculation of the OSC, whereas the total amount of CO 2 formed after several CO pulses gives the complete oxygen storage capacity of the material (OSCC).…”
Section: Characterization Of Au/ceo 2 Catalysts Involved In Oxidationmentioning
confidence: 99%
“…Indeed, it turns out that ceria is a promoter for these noble metals in the "water gas shift" reaction [21]. Studies have shown a significant metal support interaction in the case of noble metal catalysts supported on ceria (Courtois et al;Shelef and Graham 1994;Bunluesin et al 1998;Daturi et al 2001;Wang et al 2017;Koga et al 2018). They showed that this metal support interaction creates active oxygen species facilitating oxidation of CO.…”
Section: No Conversion With or Without Water In The Gas Streammentioning
confidence: 99%
“…Since the pioneer's works of Yao and Yu Yao [12] and of Su et al [13], redox properties of ceria and related oxides were extensively studied, firstly for applications in automotive converters [14][15][16][17], and later for various applications in synthesis chemistry [18], as anti-corrosion agent [19], etc. A detailed analysis of the literature (several hundred papers) is out of the scope of this review.…”
Section: Redox Propertiesmentioning
confidence: 99%